2020
DOI: 10.31851/dedikasi.v3i1.5340
|View full text |Cite
|
Sign up to set email alerts
|

KUPAS TUNTAS PENELITIAN PENGEMBANGAN MODEL BORG & GALL

Abstract: Kebugaran merupakan perpaduan dari aktivitas dan olahraga yang dilaksanakan di tempat olahraga, rumah atau tempat lainnya. Senam aerobik merupakan Model ini bersifat kualitatif survey dengan metode lecturing, yaitu menyampaikan ide dan gagasan serta wawasan yang dimiliki masing-masing pemateri kepada para peserta webinar. Teknik pengumpulan data dilakukan dengan wawancara melalui Google Form dan Whatsapp kepada 14 belas mahasiswa Universitas Riau yang melakukan Kuliah Metodologi Penelitian. Hasil menunjukkan b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
1
14
0
14
Order By: Relevance
“…This research refers to the design of research and development (R&D), meaning the research method used to produce the product and then test the effectiveness of the product. According to Borg and Gall (Putra et al, 2020), the design used in this study was using the design of the ADDIE learning model. This means that the ADDIE model is one of the most commonly used models in the field of learning design.…”
Section: Methodsmentioning
confidence: 99%
“…This research refers to the design of research and development (R&D), meaning the research method used to produce the product and then test the effectiveness of the product. According to Borg and Gall (Putra et al, 2020), the design used in this study was using the design of the ADDIE learning model. This means that the ADDIE model is one of the most commonly used models in the field of learning design.…”
Section: Methodsmentioning
confidence: 99%
“…This research refers to the design of research and development (R&D), meaning the research method used to produce the product and then test the effectiveness of the product. According to (Putra et al 2020), define development research as follows: "Educational Research and Development (R&D) is an industry bassed development model in which the findings of research are used to design new products and procedures which then are systematically field-tested, evaluated and refined until they meet specified criteria of effectiveness, quality, or similar standards." Research and development is a basic model of industrial development in which research discoveries are used to design new products and procedures that are systematic, evaluative, and filtered until specific criteria are found that are effective, qualified or have the same standards.…”
Section: Methodsmentioning
confidence: 99%
“…(Sudaryanto, 2020dan Fuadi, 2021. Model pengembangan penelitian yang membuat mahasiswa kreatif pada modul dan bahan ajar adalah ADDIE (Noviyanti, 2020), (Budiman, 2020), (Sugiyono, 2019) dan (Putra, 2020). Model penelitian pengembangan menggunakan tahap merancang (Design) untuk pembuatan instrumen validasi expertreview.…”
Section: Pendahuluanunclassified